A Combination of Real-World Experiments and Augmented Reality When Learning about the States of Wax-An Eye-Tracking Study - Sabrina Syskowski; Johannes Huwer (MDPI AG, 2023)
Burning candles show the solid and liquid states of wax on a macroscopic level. With augmented reality, the submicroscopic and symbolic level of all three states of wax can be shown. The augmented reality environment developed in this study lets students test their knowledge about the position of the three states of wax. So far, how the design parameters of augmented reality learning environments influence users' eye movement and learning performance has not been researched. Twenty-three German students between the ages of 9 and 15 form the randomized sample of this study with three different groups. AR learning scenarios were created, varying only in one design parameter: 'congruence with reality'. Our analysis using audio, video, and eye-tracking data showed that all the participants learned mostly the same and that the participants who saw the real experiment on screen experienced the highest degree of immersion. This study indicates that the presented AR learning environment is an opportunity to learn about what exact part of a candle is burning with the submicroscopic level shown in comparison; before using the learning environment, the students were uncertain about what substance burns when a candle is lit and what function the wick has. This study suggests teachers should think about implementing learning environments such as this to help students connect different levels of representation.